2018
DOI: 10.1149/2.0181815jes
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-Dependent Kinetics and Reaction Mechanism of Ammonia Oxidation on Pt, Ir, and PtIr Alloy Catalysts

Abstract: We report here a kinetic study of ammonia oxidation reaction (AOR) on carbon supported Pt, Ir, and PtIr (1:1) alloy catalysts using gas diffusion electrodes in 1 M KOH solution at temperatures up to 60 • C. Ammonia concentration was kept constant by letting Ar gas bubbling through concentrated ammonia solution before entering the cell. At 0.5 V versus reversible hydrogen electrode, the currents normalized to the mass of platinum group metals are in the order of PtIr > Ir > Pt. Compared to Pt, Ir exhibited high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
46
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 59 publications
(51 citation statements)
references
References 28 publications
3
46
0
2
Order By: Relevance
“…[ 225 ] It is important to note that the inactive intermediate of *N can poison the catalyst surface, following the conclusions reported by experiments. [ 21,229,230 ] Another important study by Novell‐Leruth and co‐workers indicated that NH 3 and the intermediate *NH 2 were more stable on Pt(100) than on Pt(111), suggesting structure sensitivity for the AOR process at the Pt surface. [ 231 ] They also predicted that the most probable adsorption configurations are different for various intermediates such as top sites for NH 3 , bridge sites for *NH 2 , and hollow sites for *NH and *N on Rh, Pd, and Pt.…”
Section: The Aor For Direct Ammonia Fuel Cellsmentioning
confidence: 99%
See 4 more Smart Citations
“…[ 225 ] It is important to note that the inactive intermediate of *N can poison the catalyst surface, following the conclusions reported by experiments. [ 21,229,230 ] Another important study by Novell‐Leruth and co‐workers indicated that NH 3 and the intermediate *NH 2 were more stable on Pt(100) than on Pt(111), suggesting structure sensitivity for the AOR process at the Pt surface. [ 231 ] They also predicted that the most probable adsorption configurations are different for various intermediates such as top sites for NH 3 , bridge sites for *NH 2 , and hollow sites for *NH and *N on Rh, Pd, and Pt.…”
Section: The Aor For Direct Ammonia Fuel Cellsmentioning
confidence: 99%
“…[ 236 ] Alloying Pt with other metals also generates significant benefits for improving the AOR, [ 247,257,258 ] due to electronic structure change (increase in Pt d‐electron vacancies), geometric transformation (decrease in the PtPt bond distance), and mitigating surface segregation. Currently, a variety of bimetallic PtM alloys includes Pt–Ir, [ 21,229 ] Pt–Ru, [ 259 ] Pt–Pd, [ 260 ] Pt–Rh, [ 237 ] Pt–Ni, [ 261 ] Pt–Cu, [ 262 ] and Pt–Au, [ 263 ] as well as ternary Pt alloys such as Pt–Ir–Rh, [ 110 ] Pt–Ir–Zn, [ 247 ] Pt–Pd–Rh, [ 264 ] Pt–Ir–Ni, [ 243 ] and Pt–Cu–Ru. [ 248 ]…”
Section: The Aor For Direct Ammonia Fuel Cellsmentioning
confidence: 99%
See 3 more Smart Citations